The Doctrine of Double Effect and Medical Ethics: A New Formulation - Sharifzadeh, Rahman (ETHICS IN PROGRESS, 2022)
The standard version of the doctrine of double effect, a significant doctrine in applied ethics particularly medical ethics, not only fails to capture some morally significant components of Aquinas’ view, but it does not resort to proper complementary features in order to accommodate the doctrine to our moral intuitions. We attempt to offer a new formulation of the doctrine incorporating the main components of Aquinas’ view and also to extend the view using some complementary features. We will examine the strength of the formulation applying it into some ethically controversial situations, mainly in medical ethics.